Question generation behavior of reflective teachers. Issue 4 (3rd July 2016) - Tavakoli, Elaheh; Davoudi, Mohammad
Abstract: Following the significance of teachers' questions, the current mixed-method study aims to identify 20 EFL (English as a foreign language) teachers' most frequent reflective techniques based on the English Language Teacher Reflective Inventory (ELTRI), and compare the quantity of their questions based on non-participant observation of their classrooms' video recordings. Transcription and further analysis of the teachers' questions also aimed at comparing the quality of teachers' generated questions in terms of their cognitive level identified based on Bloom's taxonomy. The results of the quantitative phase showed no significant difference in the teachers' choice of 'reflective, ' 'cognitive, ' 'affective, ' 'practical, ' and 'critical' components of reflective teaching. With a very slight difference, 'metacognitive' and 'moral' components (Mean = 25.05, SD = 4.66 & 27.88, SD = 3.85 respectively) were used more frequently by teachers. Pearson correlation showed a significant relationship between teachers' reflection and the quantity of questions they generated. The qualitative phase of the study showed very little use of higher level questions in Bloom's taxonomy by four teachers, TA, MO, EL, and PO. They generated analysis, synthesis, and evaluation questions/higher level questions. However, 'knowledge, ' 'comprehension, ' and application questions were used by almost all of the teachers. Implications of the study are discussed.